EFFICACY OF ANTI-BACTERIAL COMPOUNDS AND PLANT EXTRACTS AGAINST METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS ISOLATES FROM NOSOCOMIAL INFECTIONS - M. Q. Zeshan; M. Ashraf; M. O. Omer; H. M. Khan; M. A. Ali; A. A. Anjum (Journal of Animal and Plant Sciences, 2015)
Sensitivity of Methicillin Resistant Staphylococcus aureus (MRSA) isolates purified from post operative wounds (n=100) from patients in surgical wards of Mayo, SIMS and Jinnah Hospital in Lahore-Pakistan was evaluated for antibiotics and plant extracts. The minimum inhibitory concentrations of ethanol extracts of medicinal plants (Opuntia delinii, Acacia nilotica and Aloe vera) and antibiotics (Moxifloxacillin, Cefipime, Imipenem/Cilastatin and Ampicillin+Cloxacillin) were determined by micro broth dilution method. Staphylococcus aureus isolates were identified on the basis of colonial morphology, microscopic morphology and biochemical characteristics. Resistance to Methicillin recorded was 72, 63 and 66 percent in isolates recovered from Mayo, SIMS and Jinnah hospital patients, respectively. Methanol extracts of Aloe vera, Opuntia delinii leaves, bark and leaves of Acacia nilotica were dried. Activity of Aloe vera against MRSA was highest with MIC value 32.248µg/mL followed by Acacia nilotica leaves (62.5µg/mL) and then of Acacia nilotica bark (84µg/mL). The extracts of Opuntia dillenii leaves had very low anti-MRSA activity having highest MIC value (1228µg/mL). The MIC of Moxifloxacillin and Imipenem, Cefipime and Ampicillin+Cloxacillin calculated against MRSA isolates was 2.68, 2.85, 57.81 and 11.32 µg/mL, respectively. Results of few selected anti-bacterial compounds were in close association with Linezolid (1.61 µg/mL) and Vancomycin (2.43 µg/mL).Among selected anti-bacterial agents efficacy of Moxifloxacillin, Imipenem, Ampicillin+Cloxacillin and Cefipime was comparable with standards. Both anti-bacterial compounds and extracts of studied plants may efficiently be used as alternate therapeutics against MRSA isolates.
Keywords: Methicillin resistant Staphylococcus aureus; Plant extracts; Anti-bacterial; Minimum inhibitory concentration and Nosocomial infections